Toxicity mechanisms and synergies of silver nanoparticles in 2,4-dichlorophenol degradation by Phanerochaete chrysosporium - Huang, Zhenzhen; Chen, Guiqiu; Zeng, Guangming; Guo, Zhi; He, Kai; Hu, Liang; Wu, Jing; Zhang, Lihua; Zhu, Yuan; Song, Zhongxian (Journal of hazardous materials, 2017)
[Display omitted] •Synergies of AgNPs at low doses (0–60μM) in 2,4-DCP biodegradation were observed.•Maximum degradation rates of 2,4-DCP were more than 94% at low-level AgNPs.•AgNPs-mediated toxicity to P. chrysosporium arised from the “Trojan-horse” effects.•2,4-DCP was completely degraded into CO2 and H2O at optimum conditions.•Amino, carboxyl, carbonyl and sulfur-containing groups assist in Ag transportation. Mechanisms of silver nanoparticles-mediated toxicity to Phanerochaete chrysosporium and the influence of silver nanoparticles (AgNPs) on the biodegradation of 2,4-dichlorophenol (2,4-DCP) have been systematically investigated. AgNPs at low doses (0–60μM) have greatly enhanced the degradation ability of P. chrysosporium to 2,4-DCP with the maximum degradation rates of more than 94%, exhibiting excellent synergies between AgNPs and P. chrysosporium in the degradation of 2,4-DCP. Meanwhile, removal of total Ag was also at high levels and highly pH dependent. However, significant inhibition was highlighted on 2,4-DCP biodegradation and Ag removal upon treatment with AgNPs at high doses and AgNO3 at low-level exposure. Results also suggested that AgNPs-induced cytotoxicity could arise from the “Trojan-horse” mechanism executing particle effects, ion effects, or both, ruling out extracellularly released Ag+. Moreover, under relatively low concentrations of AgNPs exposure, 2,4-DCP was broken into linear chain organics, and eventually turned into CO2 and H2O through reductive dechlorination and reaction with hydroxyl radicals. FTIR analysis showed that amino, carboxyl, carbonyl, and sulfur-containing functional groups played crucial roles in Ag transportation and the reduction of Ag+ to Ag0.